(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2023)
The article provides information about the influence of natural climatic conditions on the design of buildings and structures. The author emphasizes that design and construction, taking into account the local climate conditions, based on the characteristics and functional requirements of the building or structure being designed, allows to find an effective solution. It is necessary to take into account various factors when designing the architectural construction solutions of the project object: i.e. air temperature, solar radiation, humidity, wind speed, precipitation. It is desirable to find a solution using modern technical means in the construction of new architectural forms, original planning projects.